2018
DOI: 10.1155/2018/4234256
|View full text |Cite
|
Sign up to set email alerts
|

Early Infant Diagnosis Sample Management in Mashonaland West Province, Zimbabwe, 2017

Abstract: Background In 2016, Mashonaland West Province had 7.4% (520) dried blood spot (DBS) samples for early infant diagnosis (EID) rejected by the Zimbabwe National Microbiology Reference Laboratory (NMRL). The samples were suboptimal, delaying treatment initiation for HIV-infected children. EID is the entry point to HIV treatment services in exposed infants. We determined reasons for DBS sample rejections and suggested solutions. Methods A cause-effect analysis, modelled on Ishikawa, was used to identify factors im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…These findings were similar to the findings of another study conducted in Kwazulu Natal province in South Africa where the rejection rate was 4% [6]. Even higher aggregated EID program DBS rejection rate of 7.4% was reported in similar study conducted in Zimbabwe in 2017 in Mashonaland West province [10]. However, the latter was a smaller study looking at only one province compared to the current study that looked at five provinces.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These findings were similar to the findings of another study conducted in Kwazulu Natal province in South Africa where the rejection rate was 4% [6]. Even higher aggregated EID program DBS rejection rate of 7.4% was reported in similar study conducted in Zimbabwe in 2017 in Mashonaland West province [10]. However, the latter was a smaller study looking at only one province compared to the current study that looked at five provinces.…”
Section: Discussionsupporting
confidence: 90%
“…The implications of the rejections may result in missed diagnostic opportunities of HIV-infected infants, loss to follow up on the infants and challenges in early initiation of HIV-positive infants on ART. DBS rejection rates contribute towards delays in accessing of laboratory results for EID testing, have serious implications on the PMTCT program and lives of infants that may be in need of life long ART [8,10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in a study conducted in Nigeria, the main reasons for rejection were poor collection technique (26.3%), improper labelling (16.4%) and insufficient blood collection (14.8%) [9]. The same study also showed that DBS collected at primary and secondary health care level were two to three times more likely to be rejected than those collected in tertiary healthcare facilities [10].…”
Section: Introductionmentioning
confidence: 95%